Nanoherbals in Human Healthcare: A Proposed Research and Development Roadmap II - S Ahmad; U Hashim (ASEAN Journal on Science and Technology for Development, 2012)
Bioactive secondary metabolites derived from herbs are examined for their suitability of conversion into nanoforms having flexible morphological controls, surface stabilizations and surface functionalization. This can lead to stable chemical conjugations based on molecular recognition for their possible applications in the form of smart pharmaceuticals, nutraceuticals, cosmaceuticals and many other related areas of human healthcare using green chemistry routes. Using the principles of nanoscience and technology in association with genomics and proteomics, an attempt has been made to decipher whether a suitable form of drug discovery and targeted drug delivery like schemes are feasible in case of such nano phytochemicals using various kinds of nanosize carriers and labelling molecules already identified in the course of investigations of contemporary single molecule drug developments. Additional efforts can clarify whether such species will be successful in the early detection of diseases based on marker molecules. Once identified, these green phytochemicals will certainly replace many hazardous chemical compounds by their environmentally friendly and sustainable forms in times to come.